Clinical analysis of atrial fibrillation in pregnant women - H. F. Zhang; J. Zhang; D. Yang; S. N. Li (IMR Press, 2020)
Objective: To analyze the clinical characteristics and risk factors for the major adverse cardiovascular events (MACEs) of atrial fibrillation (AF) in pregnant women. Materials and Methods: A retrospective analysis was performed on 35 pregnant women with AF, who were treated at Beijing Anzhen Hospital, Capital Medical University, from January 2004 to May 2017. All pregnancies were recorded. Chi-squared test analysis was performed to determine the correlation between clinical factors and MACEs. Results: There were 11 cases of MACEs (31.4%), including 10 cases of heart failure (HF) and 1 case of cerebral infarction. We found 7 clinical factors with a clear correlation with the occurrence of MACEs during pregnancy: a medical history of heart operation (P = 0.0011) and AF before pregnancy (P = 0.0281), New York Heart Association (NYHA) class (P < 0.0001), a left ventricular ejection fraction (LVEF) ≤ 50% (P = 0.0055), and a delivery time < 37 weeks (P = 0.0037). The AF subtype and delivery mode have no correlation with MACEs. Conclusion: AF in pregnant women is dangerous for pregnancy and delivery, multi-disciplinary management of obstetricians, cardiologists, and neonatologists are crucial for these patients throughout pregnancy.